1995
DOI: 10.1039/c39950001143
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the full structure and absolute stereochemistry of the antifungal agent FR-900848: an X-ray crystallographic study of (1R,3S,4R,6S,7S,9R,10S,12R)-quatercyclopropyl-1,12-dimethanediyl di-4-bromobenzoate

Abstract: Degradation studies and partial synthesis are used t o establish the full structure and absolute stereochemistry of the nucleoside antifungal agent FR-900848.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…These conformations must result from energetic compromises between intramolecular van der Waals interactions between hydrogen atoms or simply from crystal packing effects. It is noteworthy that such a conformation has never been observed in the solid state for either of the quater‐ or quinquecyclopropane derivatives along the routes to FR‐900848 ( 1 ) (all‐ gauche conformation10b, 12) and to U‐106305 ( 2 ) ( gauche / trans / gauche / gauche conformation13c), or the macrocyclic compounds containing a quinquecyclopropane fragment (predominating trans / trans / gauche / trans conformation15a).…”
Section: Resultsmentioning
confidence: 99%
“…These conformations must result from energetic compromises between intramolecular van der Waals interactions between hydrogen atoms or simply from crystal packing effects. It is noteworthy that such a conformation has never been observed in the solid state for either of the quater‐ or quinquecyclopropane derivatives along the routes to FR‐900848 ( 1 ) (all‐ gauche conformation10b, 12) and to U‐106305 ( 2 ) ( gauche / trans / gauche / gauche conformation13c), or the macrocyclic compounds containing a quinquecyclopropane fragment (predominating trans / trans / gauche / trans conformation15a).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, use of dioxaborolane 13 gave the quatercyclopropane 41 (100%). It was apparent from 1 H and 13 C NMR data that the quatercyclopropanes 40 and 41 were two different C 2 -symmetric isomers, and we rigourously established structures by an X-ray crystallographic study 25 of the bis(4bromobenzoate) ester derived from 40 (Fig. 2).…”
Section: Stereoselective Syntheses Of Quatercyclopropanes and The Ste...mentioning
confidence: 85%
“…We have explored three strategies for the stereoselective construction of quatercyclopropane arrays: (i) a double Yamamoto cyclopropanation followed by a double Charette cyclopropanation, 9,25 (ii) a double Charette cyclopropanation followed by a second double Charette cyclopropanation, 26 and (iii) a tetraene tetracyclopropanation reaction. 21 In the first approach (Scheme 7), acid catalysed hydrolysis of the diacetal 33 gave the corresponding dialdehyde, which was directly homologated using a double Wittig reaction to provide a mixture of the E,Ediester 37 and the E,Z-diester 38 (3.7 : 1).…”
Section: Stereoselective Syntheses Of Quatercyclopropanes and The Ste...mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Herein we report full experimental details for the structural elucidation of FR-900848 (1) which was previously reported in communication format. [11][12][13][14] These studies were an essential prerequisite for our total synthesis of FR-900848 (1) also recently reported. 15 After the communications we have published on FR-900848 (1) [11][12][13][14] and during the drafting of this paper, Kuo et al have reported on the isolation and structural determination of U-106305 (8).…”
Section: Introductionmentioning
confidence: 99%